Ni3+-induced formation of active NiOOH on the spinel Ni-Co oxide surface for efficient oxygen evolution reaction - Wang, Hsin-Yi (2015)
Efficient and earth abundant electrocatalysts for high-performance oxygen evolution reaction (OER) are essential for the development of sustainable energy conversion technologies. Here, a new hierarchical Ni–Co oxide nanostructure, composed of small secondary nanosheets grown on primary nanosheet arrays, is synthesized via a topotactic transformation of Ni–Co layered double hydroxide. The Ni3+-rich surface benefits the formation of NiOOH, which is the main redox site as revealed via in situ X-ray absorption near edge structure and extended X-ray absorption fine structure spectroscopy. The Ni–Co oxide hierarchical nanosheets (NCO–HNSs) deliver a stable current density of 10 mA cm−2 at an overpotential of ≈0.34 V for OER with a Tafel slope of as low as 51 mV dec−1 in alkaline media. The improvement in the OER activity can be ascribed to the synergy of large surface area offered by the 3D hierarchical nanostructure and the facile formation of NiOOH as the main active sites on the surface of NCO–HNSs to decrease the overpotential and facilitate the catalytic reaction.